2017
DOI: 10.1111/apt.13931
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation of colonic microbiota to galactooligosaccharides: a proof‐of‐concept‐study

Abstract: The availability of substrates induces an adaptation of the colonic microbiota activity in bacterial metabolism, which produces less gas and associated issues. Clinical trials.gov NCT02618239.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 39 publications
(92 reference statements)
5
39
1
Order By: Relevance
“…Indeed, gas homeostasis occurring within a week of administration with B-GOS®, as a result of metabolic and compositional microbiota changes was previously shown in adults. 29,30 Thus, it is not unreasonable to suggest that its positive effect in reducing the GI symptoms in the current study, can be contributed to its positive effect on microbiota and specifically bifidobacteria.…”
Section: Fodmapsmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, gas homeostasis occurring within a week of administration with B-GOS®, as a result of metabolic and compositional microbiota changes was previously shown in adults. 29,30 Thus, it is not unreasonable to suggest that its positive effect in reducing the GI symptoms in the current study, can be contributed to its positive effect on microbiota and specifically bifidobacteria.…”
Section: Fodmapsmentioning
confidence: 74%
“…[23][24][25][26][27] In IBS sufferers, it reduced bloating and abdominal pain without changes to their diets, 28 and in healthy adults, it was shown not to result in GI symptoms. 29,30 The aim of the current study was to understand the effect of B-GOS® administration to adults selected from the general population who often suffer with bloating, abdominal pain, or flatulence but who are not formally diagnosed with IBS or other forms of FBD, in a double-blind, placebo-controlled, cross-over study.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study carried out in healthy subjects noted that while flatulence does initially increase after supplementation with β‐GOS, levels return to baseline within a couple of weeks (Mego et al . ). Gas production correlated with changes in the gut microbiota, which likely resulted in less gas being produced and more being consumed by microbes.…”
Section: Potential Health Effects Of Prebioticsmentioning
confidence: 97%
“…A randomized, double-blind study of healthy individuals with mild functional bowel symptoms demonstrated that regular consumption of short-chain FOS 5 g/day reduced the frequency and intensity of digestive symptoms and improved intestinal discomfort and QOL compared with placebo after 6 weeks [68]. Others have proposed that use of prebiotics may lead to short-term, potentially deleterious alterations in the microbiota, as was suggested by an increased number and volume of anal gas evacuations 2 days after initiation of supplementation with GOS by healthy individuals; however, after 3 weeks, the number and volume of evacuations decreased to pretreatment levels, suggesting that gut microbiota adapted to the prebiotics [69]. In this study, bifidobacteria abundance increased significantly from baseline to days 3 and 21 (P = 0.04 and P = 0.03, respectively, vs. baseline) for healthy individuals with bifidobacteria abundance <0.5% of total bacteria at baseline [69].…”
Section: Prebioticsmentioning
confidence: 99%
“…Others have proposed that use of prebiotics may lead to short-term, potentially deleterious alterations in the microbiota, as was suggested by an increased number and volume of anal gas evacuations 2 days after initiation of supplementation with GOS by healthy individuals; however, after 3 weeks, the number and volume of evacuations decreased to pretreatment levels, suggesting that gut microbiota adapted to the prebiotics [69]. In this study, bifidobacteria abundance increased significantly from baseline to days 3 and 21 (P = 0.04 and P = 0.03, respectively, vs. baseline) for healthy individuals with bifidobacteria abundance <0.5% of total bacteria at baseline [69]. Using prebiotics to enhance the growth of bifidobacteria seems logical to reduce symptoms of IBS; however, studies are limited by the type and dose of prebiotic used.…”
Section: Prebioticsmentioning
confidence: 99%